Construction of Brauer-Severi Varieties (Contemporary Mathematics, 2021)
In this paper, we give an algorithm for computing equations of Brauer-Severi varieties over fields of characteristic 0. As an example, we show the equations of all Brauer-Severi surfaces defined over Q.
Keywords: Brauer-Severi varieties, twists, central simple algebras, Veronese embedding, Hilbert's Theorem 90